2016
DOI: 10.1155/2016/7349371
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAdherence of Oral Bacteria to Different Types of Tongue Piercings

Abstract: The purpose of this work was to verify in vitro adherence of E. corrodens and S. oralis to the surface of tongue piercings made of surgical steel, titanium, Bioplast, and Teflon. For this, 160 piercings were used for the count of Colony Forming Units (CFU) and 32 piercings for analysis under scanning electron microscopy. Of these, 96 (24 of each type) were individually incubated in 5 mL of BHI broth and 50 μL of inoculum at 37°C/24 h. The other 96 piercings formed the control group and were individually incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Moreover, the present results clearly demonstrated that the clinicoradiographic parameters of periodontal and peri‐implant inflammation were poorer in patients using tongue ornaments manufactured from bioplastic material compared with stainless steel. In an in ‐ vitro study, Borges et al 31 assessed the adherence of Streptococcus oralis ( S. oralis ) and Eikenella corrodens ( E. corrodens ) to the surface of tongue piercings fabricated from stainless steel and Bioplast materials. The results showed that the adherence of S. oralis and E. corrodens was higher on bioplastic materials compared with stainless steel 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the present results clearly demonstrated that the clinicoradiographic parameters of periodontal and peri‐implant inflammation were poorer in patients using tongue ornaments manufactured from bioplastic material compared with stainless steel. In an in ‐ vitro study, Borges et al 31 assessed the adherence of Streptococcus oralis ( S. oralis ) and Eikenella corrodens ( E. corrodens ) to the surface of tongue piercings fabricated from stainless steel and Bioplast materials. The results showed that the adherence of S. oralis and E. corrodens was higher on bioplastic materials compared with stainless steel 31 .…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSS IONAccording to the results of the present investigation, individuals with tongue piercings demonstrated worse periodontal and peri-implant inflammatory conditions around teeth and implants, respectively, located in the anterior mandible compared with other jaw locations.Moreover, the present results clearly demonstrated that the clinicoradiographic parameters of periodontal and peri-implant inflammation were poorer in patients using tongue ornaments manufactured from bioplastic material compared with stainless steel. In an in-vitro study, Borges et al31 assessed the adherence of Streptococcus oralis (S. oralis) and Eikenella corrodens (E. corrodens) to the surface of tongue piercings fabricated from stainless steel and Bioplast materials. The results showed the adherence of S. oralis and E. corrodens was higher on bioplastic materials compared with stainless steel 31.…”
mentioning
confidence: 99%
“…За даними L.P. Borges із співавт. [5], за пірсингу язика медична сталь нарівні з титаном показала низьку ступінь бактеріальної адгезії порівняно з біопластом і тефлоном. Таким чином, можна вважати актуальним напрям досліджень клініко-морфологічних змін у тканинах язика та щоки при експериментальному пірсингу з медичної сталі на тваринах та подальшою оцінкою наслідків даної процедури.…”
Section: вступunclassified
“…Одним з основних ускладнень цукрового діабету, який може призвести до інвалідизації хворих, є діабетична ретинопатія (ДР). [1,2,3,4,5,6], Під час розвитку цієї мікросудинної патології відбувається ураження судин сітківки із подальшим утворенням мікроаневризм, крововиливів та можливим новоутворенням судин на очному дні. І як наслідок цих патофізіологічних зрушень знижується гострота зору та розвивається сліпота [7,8,9,10,11,12].…”
Section: вступunclassified
“…It must also be understood that in the world of dental jewelry, the line between aesthetics and potential risks can be very thin given the risks associated with invasive jewelry like piercings. [34][35][36][37][38][39][40][41] Dentists have a moral obligation to weigh the aesthetic benefits against the harm that might be caused due to the placements of the jewelry. Careful and judicial counseling and guidance in the choice of the type of jewelry is imperative -to make sure that "this thing of beauty will be a joy forever.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%